Prey selectivity of bacterivorous protists in different size fractions of reservoir water amended with nutrients - Jezbera, Jan; Hornák, Karel; Simek, Karel (Environmental microbiology, 2006)
An experiment designed to examine food preferences of heterotrophic nanoflagellates (HNF) grazing on bacterioplankton was performed in the freshwater Rímov reservoir (Czech Republic). Water samples were size-fractionated to obtain < 5 microm filtrate containing bacteria and HNF. To manipulate resource availability, < 5 microm treatments were incubated in dialysis bags submerged in the barrels filled with the unfiltered reservoir water amended with either orthophosphate or glucose or combination of both. We employed rRNA-targeted probes to assess HNF prey preferences by analysing bacterial prey in HNF food vacuoles compared with available bacteria. Actinobacteria (the HGC69a probe) were avoided by HNF in all treatments. Cytophaga-Flavobacterium-Bacteroidetes bacteria (the CF319a probe) were positively selected mainly in treatments in which bacteria were heavily grazed, the < 5 microm treatments, but this trend was less pronounced towards the end of the study. The members of a small subcluster of Betaproteobacteria (the R-BT065 probe) were mostly positively selected. The nutrient amendments differentially affected bacterioplankton dynamics in almost all treatments, and together with the size fractionation, altered HNF overall bacterivory as well as prey selection. Analyses of bacterivores in unfiltered treatments allowed to detect the effect of different protists on shifts in HNF selectivity observed in < 5 microm compared with unfiltered treatments.
Keywords: Animals; Proteobacteria; fosfor; druhová specificita; RNA, Ribosomal, 16S; stravovací zvyklosti; Zooplankton; Predatory Behavior; Species Specificity; Fresh Water; Feeding Behavior; Phosphorus; sladká voda; glukosa; Glucose; Actinobacteria; hybridizace in situ fluorescenční; predátorské chování; zvířata; zooplankton; In Situ Hybridization, Fluorescence; RNA ribozomální 16S; Eukaryota